An alien spectator of the works "Sursum Corda" and "Walhalla", by Anselm Kiefer - Costa, Samuel de Oliveira (Revista do Colóquio, 2025)
Based on the works Sursum Corda (2016) and Walhalla (1992–2016), by Anselm Kiefer, this article seeks to reflect on the perception of an alien spectator, disconnected from historical, religious or mythical references associated with the artist. Based on the philosophy of Arthur Schopenhauer and the complex thought of Edgar Morin, it is argued that the aesthetic experience can reveal the artist’s poetic intuition, operating as an open system of meaning and sensitive manifestation of the Will.